2005
DOI: 10.1002/jso.20273
|View full text |Cite
|
Sign up to set email alerts
|

Surgery promotes implantation of disseminated tumor cells, but does not increase growth of tumor cell clusters

Abstract: The (post) surgical intra-peritoneal microenvironment enhances successful implantation of spilled tumor cells, whereas growth of adhered tumor cell clusters is not affected. The inflammatory response as a result of remote surgery promotes successful tumor development as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Thus, no surgical manipulation was performed. However, studies have demonstrated that surgical manipulation represents the most important factor in peritoneal tumor dissemination [40,41]. In the future, it should be investigated whether surgical manipulation in the setting of different surgical environments, including laparotomy and CO 2 pneumoperitoneum, affect tumor growth and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no surgical manipulation was performed. However, studies have demonstrated that surgical manipulation represents the most important factor in peritoneal tumor dissemination [40,41]. In the future, it should be investigated whether surgical manipulation in the setting of different surgical environments, including laparotomy and CO 2 pneumoperitoneum, affect tumor growth and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surgery-associated inflammatory reactions are not limited to the resection area but spread out systemically (12,13). Even enhanced tumor recurrence at distant sites has been observed after surgery (14). Elevated levels of the proinflammatory cytokines interleukin (IL)-1, IL-6, and tumor necrosis factor a (TNFa) in the peripheral blood after major abdominal surgery have been described (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study, Busch et al [1] suggested an association between recurrent tumour disease and extent of surgical injury. It has also become evident from experimental studies [2, 3] that enhanced tumour cell adherence and tumour growth are inevitable repercussions of surgical peritoneal trauma. The pathogenesis of the processes responsible for postoperative intra-abdominal tumour recurrence is only partly clarified.…”
Section: Introductionmentioning
confidence: 99%